Understanding the motivation to invest: a profile analysis of Islamic funds' investors - Barom, Mohd Nizam (Universiti Sains Islam Malaysia, 2019)
This paper seeks to provide a preliminary profile analysis of investors of Islamic funds based on their underlying motivation to invest, which at present received little interest in the literature. The experience of faith-based and socially responsible investment clearly reveals the heterogeneity of investors with divergent investment motives, and this is highly likely to be true among Islamic funds’ investors as well. For this purpose, the study surveys Investors of Islamic funds from three fund management companies in Malaysia with a total sample of 451 respondents. The profiling employs a cluster analysis of the respondents using religion, percentage invested in Islamic funds, and four potential motivations to invest. The result shows a possible segmentation of the investors into three groups, with Muslim investors being segmented into two categories, ‘committed’ and ‘pragmatic’ investors, while the third category being the ‘non-Muslim’ investors. The clusters represent a clear distinction between the three groups in terms of their commitment to Shari’ah principles in investment, the importance of earning halal vis-à-vis high returns, and the benefits of diversification between Islamic and conventional funds. The findings provide valuable insights for fund management companies in terms of understanding the different segments of investors and their issues of concerns for better investment services, product innovation and offering, as well as marketing strategies.